The tandem repeat modules of Xist lncRNA: a swiss army knife for the control of X-chromosome inactivation - Raposo, Ana Cláudia (2022)
© 2021 The Author(s) This is an open access article published by Portland Press Limited on behalf of the Biochemical Society and distributed under the Creative Commons Attribution License 4.0 (CC BY).